Institutional and Legal Aspects in Land Disputes: the Context of Nepalese Cadastral Surveying (Journal on Geoinformatics, Nepal, 2008)
Cadastral Surveying is the foundation of land administration and management activities in Nepal. The country has nationwide coverage of cadastral surveying achieved by conducting systematic cadastral surveying from 1964 to 1997. Cadastral re-surveying has been initiated since 1994. Some of the cases of land disputes that exist in Nepalese society are due to inadequacy of cadastral surveying activities in various aspects, institutional and legal aspects are two of them. Some weaknesses of existing institutional set up and legal framework that are in! uencing the attempts to resolve the disputes such as limited authorities to the organisation involving in systematic cadastral surveying, lacking proper coordination among the district level stakeholder organisations, lacking proper mechanism for bridging the incompleteness of cadastral surveys conducted by commissions/committees, lacking comprehensive legal documents, ambiguous legal provisions, etc have been pointed out in the paper.